2017
DOI: 10.1159/000478779
|View full text |Cite
|
Sign up to set email alerts
|

A History of Cow’s Milk Allergy Is Associated with Lower Vitamin D Status in Schoolchildren

Abstract: Background/Aims: Vitamin D insufficiency is common in children. We aimed to evaluate the main determinants of vitamin D status in Finnish school-aged children, including the history of allergic diseases. Methods: We conducted a cross-sectional study on 171 ten-year-olds where serum 25-hydroxyvitamin D (25[OH]D) levels were measured, and data on food consumption and use of vitamin D supplements were collected. The history of allergic diseases was evaluated with a validated questionnaire. Results: Vitamin D insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…As previously mentioned, three out of four adolescents in Northern Norway had 25(OH)D <50 nmol/l [43]. In Finland, a study among 10-year-olds showed adequate mean 25(OH)D concentrations and 16% had 25(OH)D ˂50 nmol/l [52]. In a study of Finnish newborn infants living in the metropolitan area, only 1% had inadequate cord blood 25(OH)D concentration [53].…”
Section: Adults and Older Adultsmentioning
confidence: 85%
“…As previously mentioned, three out of four adolescents in Northern Norway had 25(OH)D <50 nmol/l [43]. In Finland, a study among 10-year-olds showed adequate mean 25(OH)D concentrations and 16% had 25(OH)D ˂50 nmol/l [52]. In a study of Finnish newborn infants living in the metropolitan area, only 1% had inadequate cord blood 25(OH)D concentration [53].…”
Section: Adults and Older Adultsmentioning
confidence: 85%
“…Children who drank at least 450 g/day of vitamin D-fortified milk had a 72–74% lower risk of having S-25(OH)D below 50 nmol/L than those who drank less than 300 g/day (adjusted for age and sex). However, another study on 10-year-old Finnish children ( n = 171) found no association between vitamin D-fortified milk consumption frequency and S-25(OH)D status, but among those children with a history of cow’s milk allergy (an indicator of milk avoidance), consumption of vitamin D-fortified milk as well as S-25(OH)D concentrations were lower than among their peers without allergy history [ 45 ]. Nevertheless, vitamin D supplement use was very common in this population (60% daily users), and thus was one important determinant of their vitamin D status [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…For vitamin D, a blood assay may detect insufficient levels, but supplementing the child throughout the elimination diet is common practice. The vitamin D status was significantly lower in Finnish schoolchildren with a history of CMPA, indicating that restricting the diet may have long-term consequences on dietary habits and subsequently on later vitamin D status [26]. Calcium supplements may be used if intakes remain below the daily need.…”
Section: The Need For a Precise Dietary Follow-upmentioning
confidence: 99%